Exports and firm profitability: Quality matters! - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper uses a tailor-made newly available data set to investigate for the first time the links between profitability and the quality of exports in enterprises from manufacturing industries in Germany, one of the leading actors on the world market for goods. The paper demonstrates that exporters of high-quality goods tend to be more profitable.
Keywords: F14; 330; Exports; export quality; profitability; Germany